Exploring The Application of KWL Strategy Towards Students’ Reading Comprehension: Teachers’ Perceptions - Dodi Widia Nanda; Deded Pratama (Journal of English Language Studies, 2021)
This research aims to explore the benefits of Know, Want and Learn (KWL) strategy towards students’ reading comprehension, particularly in English Language Teaching (ELT). The chosen topic is selected due to the students’ difficulties in comprehending English texts, showing that learners’ lack of motivation and reading interests and the ineffective teaching method offered.  Additionally, this paper applies semi-structured interview to collect data, interviewing 3 English teachers in regard to the implementation of KWL strategy in the teaching and learning of reading comprehension. The research’s result shows that KWL strategy boosts students’ engagement and understanding. It also enhances students’ concentration and grades in reading comprehension. It would be a sensible idea for teachers to apply an interactive learning process and deeper exploration concerning this topic is required as well in upcoming investigations